Nauczyciel – Mistrz, czyli „strategia przebudzenia” z totalitarnego snu ("Zielony namiot" Ludmiły Ulickiej) - Duda, Katarzyna (Rusycystyczne Studia Literaturoznawcze, 2016)
The novel The Green Pavilion includes plenty of different issues — among them a function of a teacher plays the most important part. This job was especially difficult in Soviet country where censorship and ideology were very strong. Teachers were afraid of communistic government and they worked in a bad way, telling lies, deceiving students or teaching only these things which were allowed by officials. However, Ulitskhaya shows that “good teachers” also acted under those circumstances. They were the members of a generation who took part in the Second World War and that is way they were aware of many dangers, moreover: they began independent which was strictly forbidden in the former USRR. Victor Yulyevitsh Shenghely is the best example of these kind of educators described in Ulitskhaya’s novel. Not only does he pass on the knowledge but he brings up his pupils properly as well. Children love and admire him. Shenghely became real authority. He meets his student both in the classroom and in his flat, in school and in the Moscow street which is treated by him as a special kind of museum together with its monuments, theatres and homes where famous Russian poets and writers lived in the past. In this way Victor comes back to ttadition destroyed by Bolsheviks. He explains the great importance of literature in totalitarian life. He treats this kind of art as means of telling the truth, as a possibility of expressing facts not lies. Shenghely wants students to be his partners. He respects them and they rely on him talking about their problems which seem to be difficult to overcome. The main Victor’s characteristics — responsibility, cleverness, courage — help him to bring up dissidents. The author of The Green Pavilion emphasizes that masters like Shenghely should exist both in the modern times as well as in the future.